Effect of SP-36 and Aloe Vera POC on Pre Nursery Oil Palm Seedlings - Mulyanti , Mulyanti; Mukmini, Oktarisa Nurul; Nitariani, Nitariani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Fertilization is one of the most important maintenance activities for the growth of pre-nursery oil palm seedlings. This study aims to determine the effect of SP-36 fertilizer and aloe vera POC on the growth of oil palm seedlings. This study used a non-factorial Randomized Group Design (RAK) with 5 treatments and 5 replicates so that 25 experimental units were obtained, with the treatment sequence namely P0 = Without SP-36 Fertilizer and Aloe Vera POC, P1 = SP-36 fertilizer 5 g/plant + POC Aloe Vera 50 ml/plant, P2 = SP-36 fertilizer 10 g/plant + POC Aloe Vera 100 ml/plant, P3 = SP-36 fertilizer 15 g/plant + POC Aloe Vera 150 ml/plant, P4 = SP-36 fertilizer 20 g/plant + POC Aloe Vera 200 ml/plant. Parameters observed were the number of leaf midribs, plant height and stem diameter. The results of the analysis of variance showed that the provision of SP-36 fertilizer and POC aloe vera did not have a significant effect on the number of leaf midribs, plant height and stem diameter of pre-nursery oil palm seedlings. The best treatment was obtained in the P2 treatment (10 g SP-36 + 100 ml POC aloe vera).